2010
DOI: 10.1016/j.jacc.2009.11.095
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Plasma Fibrinolysis Activation Markers in Cardiovascular Disease

Abstract: The pivotal role of hypoactive endogenous fibrinolysis in the occurrence of thrombotic cardiovascular events is now well-recognized. To evaluate the diagnostic and prognostic role of impaired fibrinolysis, plasma fibrinolysis markers have been investigated in large prospective studies in both healthy individuals and patients with established coronary disease. Antigen and activity levels of components of the fibrinolytic system were measured by immunoassays, which replaced earlier global fibrinolysis tests. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 96 publications
1
97
1
8
Order By: Relevance
“…Various observational studies in the past have found that vegetarian diets increases the fibrinolytic activity and decreases the thrombogenic potential of blood by decreasing PAI-1, factor VII, and blood viscosity [4,10].On data analysis of present study we did not find any significant difference in fibrinolytic activity between lactovegetarian and semi-vegetarian groups [Table/ Fig-2]. This might be due to lack of representative population of different dietary classes in our study sample.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Various observational studies in the past have found that vegetarian diets increases the fibrinolytic activity and decreases the thrombogenic potential of blood by decreasing PAI-1, factor VII, and blood viscosity [4,10].On data analysis of present study we did not find any significant difference in fibrinolytic activity between lactovegetarian and semi-vegetarian groups [Table/ Fig-2]. This might be due to lack of representative population of different dietary classes in our study sample.…”
Section: Discussioncontrasting
confidence: 60%
“…This is found to be well correlated with proneness towards stroke, IHD, thrombo-embolic diseases and is an independent predictor of both fatal and nonfatal IHD [4][5][6]. Thus assessment of fibrinolysis time is one of the most important markers of cardiovascular health [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Отдельные белки могут принимать участи во всех процессах, обеспечивая взаимную регуля-цию различных этапов свертывания. В данном обзоре мы остановимся на функционировании и регуляции финального этапа существования тромба -фибри-нолизе.Нарушения в системе фибринолиза могут быть связаны с увеличением риска развития венозного тромбоза [1], но не во всех работах такая закономер-ность была обнаружена [2]. В ряде случаев, таких как инфаркт миокарда, тромбоз глубоких вен, легочная эмболия, инсульт, возникает необходимость экстрен-ного удаления тромба, препятствующего кровотоку.…”
unclassified